Logic, Rationality, and Interaction 9th International Workshop, LORI 2023, Jinan, China, October 26-29, 2023, Proceedings - Alechina, Natasha; Herzig, Andreas; Liang, Fei. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This LNCS book is part of the FOLLI book series and constitutes the proceedings of the 9th International Workshop on Logic, Rationality, and Interaction, LORI 2023, held in Jinan, China, in October 2023. The 15 full papers presented together with 7 short papers in this book were carefully reviewed and selected from 40 submissions. The workshop covers a wide range on the following topics such as agency; argumentation and agreement; belief representation; probability and uncertainty; belief revision and belief merging; knowledge and action; dynamics of informational attitudes; intentions, plans, and goals; decision making and planning; preference and utility; cooperation; strategic reasoning and game theory; epistemology; social choice; social interaction; speech acts; knowledge representation; norms and normative systems; natural language; rationality; philosophical logic.
Rationality -- Epistemology -- Agency; argumentation -- Knowledge representation -- Probability and uncertainty -- Belief revision.-Norms -- Actions -- Intentions and goals. - Game theory -- Social interaction -- Social choice -- Speech acts -- Natural language.
Keywords: Logic; Game theory; Natural language processing (Computer science).; Logic; Game Theory; Natural Language Processing (NLP).